Peran Kantor Cabang Dinas Pendidikan Wilayah XIII Provinsi Jawa Barat Pada Penerimaan Peserta Didik Baru Berbasis Online Tahun 2024 - Syahrul Apriansyah; Irfan Nursetiawan; Asep Nurdin Rosihan Anwar (Kampus Akademik Publiser, 2025)
The role of the Regional Education Office Branch Office XIII of West Java Province has an important role in facilitating and supervising the implementation of online PPDB in its region. By understanding this role, it is expected that there will be recommendations that can be given to improve the effectiveness and efficiency of the online-based PPDB system in the future. this study aims to analyse the impact of online PPDB implementation on the quality of education in the region. By examining this impact, it is expected to know the extent to which this system contributes to improving access to education for students and increasing transparency and accountability in the admission process.